2023
DOI: 10.7759/cureus.42003
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C Levels as a Predictor of Severity and Mortality Among Patients With COVID-19 Infection

Abstract: Introduction: The pandemic caused by SARS Corona Virus-2 (COVID-19) has caused widespread mortality globally. The hallmark of the disease is the "cytokine storm," which is caused due to dysregulated immune system activation. Numerous inflammatory markers are used to predict the severity and mortality of the infection. Serum Cystatin C levels are associated with immune responses to exogenous and endogenous antigens. Our study was done to assess serum cystatin C as a marker of severity and mortality among patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…By employing different grouping models, our study demonstrated that CysC was a significant evaluation indicator associated with the prognosis of COVID-19 patients, which was consistent with previous research findings (20,21,25,33,34). We further confirmed that CysC was directly connected to the occurrence of RM and SKM injury in COVID-19 patients and had a good predictive value for these patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By employing different grouping models, our study demonstrated that CysC was a significant evaluation indicator associated with the prognosis of COVID-19 patients, which was consistent with previous research findings (20,21,25,33,34). We further confirmed that CysC was directly connected to the occurrence of RM and SKM injury in COVID-19 patients and had a good predictive value for these patients.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that CysC is closely associated with the prognosis of a variety of diseases, including coronary heart disease, vascular disease, and stroke (17–19). Meanwhile, studies have shown that in hospitalized COVID-19 patients, higher serum concentrations of CysC, which may indicate one or more processes such as worsening renal function, excessive inflammation, anti-viral activity, and cytokine storm, are associated with severe illness and higher mortality (20,21). When compared with raised serum creatinine (Cr), high CysC has a better predictive value for disease severity in COVID-19 patients and can be used to identify renal function issues early (22,23).…”
Section: Introductionmentioning
confidence: 99%